Koloniträdgården - Boström, Lena (2008)
The movement of the allotment gardens reached Sweden in the beginning of the last century. The allotment gardens quickly spread among the big towns from Malmö in the south and to the far north of the country. Today, there are about 42 000 owners of allotment gardens in Sweden. This work will show the differencies and similarities comparing the original ideas of allotment gardens with how they are used today. The specific questions were; what are the reasons to acquire an allotment garden; is it used for raising vegetables and fruit or only for growing flowers; is what is cultivated there also gathered and used or is it cultivated only for the pleasure of gardening; and finally how the owners of the allotment gardens spend their time there – by cultivating the land or by recreational activities. Literature studies were made as well as an inquiry at one allotment garden area i Lund. The ideas of the original allotment gardens in the beginning of the 20th century were as much based on the need of getting out of the aparment to a healthy environment, as cultivating vegetables for economical reasons. Filling the pantries for the winter was a clear reason but strongly connected to the well-being of the soul and the body in doing it. Among the conclusions of today's inquiry, the thought of recovering is slightly more important for the allotment garden owner than the gardening itself. They grow less useful plants but are careful in harvesting the eatable fruit and vegetables grown. The time spent in the allotment garden together with the gardening give the well-being without storing up food for the winter.